Physiological response of Prorocentrum lima (Dinophyceae) to varying light intensities. Issue 1 (6th December 2017) - David, Helena; Laza-Martínez, Aitor; Kromkamp, Jacco C.; Orive, Emma
Abstract: The benthic dinoflagellate Prorocentrum lima is among the most common toxic morphospecies with a cosmopolitan distribution. This study explored if strains from different environments and different morphotypes, isolated from three locations in the Atlantic Iberian Peninsula and two from the Mediterranean Sea, showed different responses to varying light regimes, after confirming that all strains belonged to the same ribotype. Growth rates and photosynthetic parameters such as Fo, Fv /Fm, and rETRmax were analysed with a Coulter counter, a water-PAM and a fast repetition rate fluorometer. The photosynthetic properties were investigated in a high light stress experiment using strains acclimated to low light (LL) and high light (HL). The highest growth rate was 0.23 day −1 at 80 and 100 μmol photons m −2 s −1 for strains Dn150EHU and Dn60EHU, originated from different locations. Under control conditions (18°C and 90 μmol photons m −2 s −1 ), growth rate was on average 0.10 day −1 . The HL stress exposure induced photodamage to all strains and the recovery period was not sufficiently long for full recovery of Fv /Fm . However, cells acclimated to HL showed a better recovery than the LL acclimated ones. Furthermore, some assumptions are discussed in relation to strains' original location. Abstract : Growth rates of Prorocentrum lima strains from the Atlantic Iberian Peninsula and the Mediterranean sea, under several light intensities and light induced stresses, are discussed according to the strains' geographical location.